PERAN INKUBATOR BISNIS SIGER INNOVATION HUB TERHADAP PENGEMBANGAN UMKM KULINER DI BANDAR LAMPUNG - Maulana, Ibnu Arya; Agung, Maulana; Harori, M. Iqbal (Jurnal Kompetitif Bisnis, 2023)
ABSTRACTMicro, Small and Medium Enterprises (MSMEs) have an important role for the National economy. Behind such animportant role for the nation MSMEs still face various problems. This study aims to find out an in-depth picturerelated to Siger Innovation Hub business incubator services for MSME business development in the Culinary Sectorin Bandar Lampung with Reith-7S business incubator service indicators (space, shared, services, support, skilldevelopment, seed capital, and synergy). The method used in the research is a qualitative method and usesdescriptive analysis. Data collection was carried out by observing, in-depth interviews, and documentation. Theresults of this study is the services provided by the Siger Innovation Hub to tenants include consulting services,support, skill development, seed capital, synergy.. Some services are not provided optimally by Siger InnovationHub, such as the provision of space, and the provision of shared facilities.Keywords : Service, Business Incubator, Business Development, Micro, Small and Medium Enterprises (MSMEs)